2014
DOI: 10.4049/jimmunol.1300633
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Oligodendrocyte and Neuronal Marker Genes Predicts the Clinical Onset of Autoimmune Encephalomyelitis and Indicates the Effectiveness of Multiple Sclerosis–Directed Therapeutics

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a valuable model for studying immunopathology in multiple sclerosis (MS) and for exploring the interface between autoimmune responses and CNS tissue that ultimately leads to lesion development. In this study, we measured gene expression in mouse spinal cord during myelin oligodendrocyte gp35–55 peptide–induced EAE, using quantitative RT-PCR, to identify gene markers that monitor individual hallmark pathological processes. We defined a small panel of genes whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 60 publications
5
24
0
Order By: Relevance
“…Interestingly, XPro1595-treated naive mice showed increased brain expression of Chil3, which encodes a protein associated with host defense (37) and is used as a marker for beneficial alternatively activated macrophages. Previous work also shows that XPro1595 treatment induces a transient activation of immune genes in the spinal cord at the onset of EAE, in parallel to having protective effects on OLG and neuronal gene expression (50). Here, although XPro1595 treatment did not alter the numbers of Mac3-positive macrophages in early demyelinating lesions, it increased the numbers and size of macrophages containing myelin degradation products and facilitated the clearance of myelin debris and remyelination in corpus callosum lesions.…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly, XPro1595-treated naive mice showed increased brain expression of Chil3, which encodes a protein associated with host defense (37) and is used as a marker for beneficial alternatively activated macrophages. Previous work also shows that XPro1595 treatment induces a transient activation of immune genes in the spinal cord at the onset of EAE, in parallel to having protective effects on OLG and neuronal gene expression (50). Here, although XPro1595 treatment did not alter the numbers of Mac3-positive macrophages in early demyelinating lesions, it increased the numbers and size of macrophages containing myelin degradation products and facilitated the clearance of myelin debris and remyelination in corpus callosum lesions.…”
Section: Discussionsupporting
confidence: 51%
“…Consistent with this hypothesis, TNF plays dual roles during autoimmune demyelination, namely exacerbation of inflammation at the onset of disease and facilitation of the resolution of inflammation and myelin repair during ongoing disease (18,22). In agreement, selective pharmacological inhibition of soluble TNF prevents transcriptional changes associated with the onset of CNS inflammatory demyelination and protects against MOG-induced EAE (23). Therefore, it is conceivable that selective blockade of TNFR1 may minimize undesirable side effects from anti-TNF therapy.…”
Section: Foxp3mentioning
confidence: 78%
“…In support of this finding, we here provide compelling evidence in an in vivo model of NMDAinduced acute neuronal lesions that abrogation of complete TNF signaling by blocking both TNFRs is not protective, because mounting of a neuroprotective TNFR2-dependent response is prevented. However, preclinical studies in the experimental autoimmune encephalomyelitis (EAE) model (36)(37)(38) or a mouse model of spinal cord injury (39) revealed that selective neutralization of sTNF/TNFR1 signaling is neuroprotective. Of note, in the EAE model, systemic application of TNFR1-blocking antibodies proved to be therapeutically effective (40).…”
Section: Resultsmentioning
confidence: 99%